Adult Ileocecal Intussusception: A Case Report and Review - Randy Adiwinata; Sheila Adiwinata; Emerson Patulahon Simatupang; Willy Brodus Uwan; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Intussusception is a rare cause of bowel obstruction in adult patients, it represents for five percent of all age intussusception. Several different aspects were found between adult and pediatric intussusception. We report a case of 39-year-old male with bowel obstruction due to ileocecal intussusception, which firstly diagnosed as acute appendicitis. Unlike pediatric intussusception which usually manifest as classical triad signs, unspecific symptoms of adult intussusception may become diagnostic challenge. Imaging modalities such as plain abdominal radiograph and ultrasonography may aid the preoperative diagnosis in the rural hospital setting. Prompt management which involved surgical approach is warranted to prevent further complications.